Teaching culturemes through mediation in higher education - ȘCHIOPU, Lucia (Acta et Commentationes, Sciences of Education, 2025)
This article explores the role of culturemes in the process of mediation across cultures. It shows how teaching culturemes at the university level helps students not just spot these unique cultural elements, but also understand their deeper meanings and learn strategies to translate them effectively in the process of mediation. The article highlights the main translation approaches, especially the two main methods: foreignization, which keeps the original cultural flavor, and domestication, which adapts content to fit the target audience’s culture. This article describes the research design of a qualitative study titled Translating Culturemes in Stylistics, conducted within a teacher education language program. The study employed classroom observations, reflective journals, annotated student projects, and discussions to explore how students developed cultural awareness and translation strategies through mediation engagement with culturemes over one academic semester.